Report of the Railway Reforms Committee Part Xvi Management Information System - Planning Commission (Planning Commission, 1984)
In any management apparatus, decision making is of the utmost importance. Decisions at the top and at different levels, of management have been traditionally made on the basis of a plethora of data laboriously collected and compiled. This, in today’s context, has become antiquated and very often under such a system decisions are taken not on a scientific appraisal of all relevant issues and considerations, but by way of intelligent guesses and on the basis of inadequate and incomplete information.
Government of India Ministry of Railways
Government of India Ministry of Railways